Rancang Bangun E-Commerce Planet Shopify Berbasis Web Menggunakan PHP Dan MySQL - Rafi, Muhammad; Purnama, Iwan (Himpunan Dosen Gemilang Indonesia (HDGI), 2024)
The development of programming languages in the world of the internet has indeed progressed rapidly, and the presence of programming languages in website development has had a significant positive impact. Especially, the use of programming languages such as PHP and the connection with the MySQL database have become standard in creating dynamic and interactive websites. A website without dynamic database features may feel monotonous and less responsive to user needs. Therefore, most websites, including Web-based Ecommerce systems like on Planet Shopify, utilize database applications to present information more efficiently and structured. This has enabled the use of web technology to deliver data in a more dynamic and interactive manner. The importance of the PHP programming language in web development cannot be ignored. PHP not only allows developers to create dynamic web pages but also facilitates integration with the MySQL database. This combination enables the creation of efficient and responsive Web-based Ecommerce systems with the ability to easily store, manage, and display product and order data. Web-based Ecommerce systems, especially those adopting the Business to Consumer model on Planet Shopify, become highly effective solutions. The main goal is to provide ease for consumers in obtaining the services and information they need. Additionally, this system also provides convenience for online store owners to manage product data, monitor orders, and enhance overall operational efficiency. With supporting applications like PHP, MySQL, Xampp, and CSS, developers can create attractive and functional layouts to improve the user experience. Overall, the combination of the PHP programming language and MySQL in website development opens the door to evolving innovations in the world of web database programming, enhancing efficiency, user engagement, and data management capabilities.